Motion rank: applying page rank to motion data search - Choi, M.G.; Kwon, T. (The Visual Computer, 2019)
As the uses of motion capture data increase, the amount of available motion data on the web also grows. In this paper, we investigate a new method to retrieve and visualize motion data in a similar manner to Google Image Search. The main idea is to represent raw motion data into a series of short animated clip arts, called motion clip arts. Short animated clip arts can be quickly browsed and understood by people even though many of them appear at the same time on the screen. We first temporally segment the raw motion data files into short yet semantically meaningful motion segments. Then, we convert the motion segments into motion clip arts in a way that emphasizes the main motion and minimizes the data size for the efficient transmitting and processing on the web. When a user input query is received, our system first retrieves all the relevant motion clip arts by considering the input keywords and similarity between motions. Then, the retrieved results are re-ranked by our ranking algorithm developed based on the Google ImageRank algorithm. To prove the usability of our method, we build a web-based motion search system with the entire data collections of the CMU motion database. The experimental results show significant improvement, in terms of relevancy, in comparison with the simple keyword-based search interface.